Public-Private Partnerships (PPP): Between Public and Private - The Businessman as Co-Governor - Mercado Neumann, Edgardo (2015)
This document introduces us to the problems regarding the role of the state in our times and its role as a driver of development and growth of the country. To understand the mentioned role, a brief description of the evolution of the concept of State will be done, addressing the rise of public-private partnership principle, the host of public-private partnerships and the reconfiguration of the role of the state and the private investor and co-governor of such role.